2020
DOI: 10.1038/s41467-019-14242-7
|View full text |Cite
|
Sign up to set email alerts
|

The shift of phosphorus transfers in global fisheries and aquaculture

Abstract: Global fish production (capture and aquaculture) has increased quickly, which has altered global flows of phosphorus (P). Here we show that in 2016, 2:04 3:09 1:59 Tg P yr −1 (mean and interquartile range) was applied in aquaculture to increase fish production; while 1:10 1:14 1:04 Tg P yr −1 was removed from aquatic systems by fish harvesting. Between 1950 and 1986, P from fish production went from aquatic towards the land-human systems. This landward P peaked at 0.54 Tg P yr −1 , representing a large but ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 72 publications
2
26
0
3
Order By: Relevance
“…Huang et al (2020) estimated that wild and aquaculture fisheries, including finfish, crustaceans and molluscs, represented 1.1 Tg of P in 2016, which agrees very well with our estimate. However, we should note that their calculation is based on a catch of 169 Tg of biomass containing finfish, crustaceans and molluscs, while the global amount of catch we modeled is higher, 196.2 ± 57 Tg of wet weight, even though Huang et al (2020) also considers aquaculture in addition to wild captures. Our catch estimate at global peak catch likely overestimate catch (Bianchi et al, in press).…”
Section: Phosphorussupporting
confidence: 90%
“…Huang et al (2020) estimated that wild and aquaculture fisheries, including finfish, crustaceans and molluscs, represented 1.1 Tg of P in 2016, which agrees very well with our estimate. However, we should note that their calculation is based on a catch of 169 Tg of biomass containing finfish, crustaceans and molluscs, while the global amount of catch we modeled is higher, 196.2 ± 57 Tg of wet weight, even though Huang et al (2020) also considers aquaculture in addition to wild captures. Our catch estimate at global peak catch likely overestimate catch (Bianchi et al, in press).…”
Section: Phosphorussupporting
confidence: 90%
“…Modern food production is entirely dependent on the non-renewable resource phosphorous (P) [98,99]: Biogeochemical flows-mainly nitrogen and phosphorous fluxes-are seen as a planetary boundary [100] and agriculture is a major driver exceeding it [8]. The use of phosphate causes the phosphorous dilemma: while mineral fertiliser facilitated the intensification of plant production [101,102], it has results in an enormous P-input into the biosphere [16] with P as a dominant driver of eutrophication with all its adverse effects [16]. Without P recycling, food security will inevitably be violated in the long run [103], preventing us from 'living well, within the limits of our planet' [104].…”
Section: Food: Demand-side Impact Of Dietary Shiftsmentioning
confidence: 99%
“…A retrospective review 20 years later found that overall sustainability increased but dependence on marine ingredients continued [13]. Marine aquaculture raises environmental issues [14,15], e.g., the negative landward flux of the essential mineral phosphorus [16]. The alternative to marine aquaculture is freshwater aquaculture; however, freshwater aquaculture generates wastewater, especially in flow-through systems [17], and it is estimated that over 80% of global wastewater is not adequately treated [18].…”
Section: Introductionmentioning
confidence: 99%
“…Potential environmental impacts of open-cage aquaculture, such as genetic introgression of farmed salmonid in wild populations, regulatory effects of salmonid lice and viral diseases on wild salmonid populations, and the local and regional impact of nutrients and organic load and chemical usage [6][7][8][9][10][11][12][13][14] , have been identified and gradually understood. Nutrients discharged from cage aquaculture, especially phosphorus are among the most important concerns about the environmental impacts of cage aquaculture 15,16 . Mass balance models have been constructed to estimate the total and dissolved loss of nutrients to pelagic water environment and the accumulation of nutrients in sediments 1,[17][18][19] .…”
mentioning
confidence: 99%